Field notes contributed by Dennis L. Carter, November 30, 1992 - Carter, Dennis L.et al (1992)
Fall report of birds and locations contributed by Dennis L. Carter. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1992. Plustek - flatbed